Revitalisasi Kelompok Sadar Wisata (Pokdarwis) Desa Sukodono, Kecamatan Dampit, Kabupaten Malang Dalam Pengelolaan Obyek Wisata Coban Pandawa - Bramantyo Tri Asmoro; Muh Mujib Da'awi (Jurnal Pemberdayaan Masyarakat, 2020)
Tourism is one of the leading potentials in the region, especially villages, which can be maximally developed to improve community welfare. One of the attractions in Malang Regency which has tremendous potential to be developed is Coban Pandawa, which is located in Sukodono Village, Dampit District, Malang Regency. The tourism object is managed by the Kelompok Sadar Wisata (Pokdarwis) of Sukodono Village since the end of 2018, but in its journey, Pokdarwis has not understood the role, main tasks and functions of managing a tourist attraction, so that in the end pokdarwis experienced a vacuum in 2019. This community service activity aims to revitalize Pokdarwis organizations so that they can become independent and professional organizations in developing Coban Pandawa. Activities will be divided into three stages, namely, the awareness stage, the legality stage and the capacity-giving stage. The results of the community service activities were the equalization of the vision between the Sukodono Village Government and Pokdarwis, the legality of the Pokdarwis organization from the Sukodono Village Government and the Malang Regency Office of Tourism and Culture (Disparbud), and the Coban Pandawa development blueprint.